Spatio-temporal complexity of the sea surface temperatures of the Philippines - Botin, Zolah Tolentino; Del Rosario, Ricardo C.H. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2009)
By considering an ecosystem as a complex system, we show how complexity measures can be used for its analysis. Complexity is considered as a system's attribute that captures one or more aspects of the system's structure, function or dynamics. Most complexity measures are concerned with spatial complexity but for ecosystems, it is important to measure complexity not just in space but also in time. We will discuss the Spatio-Temporal Complexity algorithm (STC) developed at the Complex Systems Laboratory, Department of Geography, University of Montreal to measure the spatio-temporal complexity of digital images of ecosystems. The algorithm depends on the acquisition of a series of data collected over certain periods ot time. In this thesis, we apply the STC algorithm to the Sea Surface Temperatures (SST) of the Philippines to determine whether STC can distinguish between El Niño, La Niña and normal years.
Thesis (Master of Science in Mathematics)--University of the Philippines Diliman
Keywords: Ocean surface topography; Ecosystem management -- Philippines